2009
DOI: 10.1038/ejcn.2009.10
|View full text |Cite
|
Sign up to set email alerts
|

Assessing children's diet quality in Crete based on Healthy Eating Index: The Children Study

Abstract: Background: This study aimed to assess children's diet quality in Crete and the potential role of several socio-demographic factors related to it. Methods: Between October 2005 and March 2006, 481 primary school children were recruited from Crete. Dietary intake data was obtained using a combination of techniques comprising a 24 h recall and 3 food diaries. The Healthy Eating Index (HEI) was calculated summing the individual scores (0-10) assigned to 10 index components. Results: The majority of participants (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 36 publications
1
16
0
1
Order By: Relevance
“…†Also adjusted for maternal age, maternal education, physical activity before pregnancy, residence and total area of the house in m 2 . healthy diet is progressively being adopted (33,34) . Thus, the norms about dietary patterns are deteriorating and women have to make an effort to adjust to the new, in essence old, healthier recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…†Also adjusted for maternal age, maternal education, physical activity before pregnancy, residence and total area of the house in m 2 . healthy diet is progressively being adopted (33,34) . Thus, the norms about dietary patterns are deteriorating and women have to make an effort to adjust to the new, in essence old, healthier recommendations.…”
Section: Discussionmentioning
confidence: 99%
“…The positive association between socioeconomic position and dietary pattern has been confirmed by research carried out on different populations, using different indexes or statistical techniques to determine dietary patterns. As reviewed by Darmon et al (2008), higher values of Healthy Eating Index (Loughley et al, 2004;Angelopoulos et al, 2009;Manios et al, 2009), Diet Quality Index (Patterson et al, 1994;Lallukka et al, 2006), dietary diversity scores (Kant and Graubard, 2007), and other diet-quality measures (Groth et al, 2001;Dynesen et al, 2003;Robinson et al, 2004) have all been associated with a higher socioeconomic position, usually estimated by education level. Using principal components analysis to determine dietary patterns, Robinson et al (2004) found that educational attainment was the most important determinant of a healthy eating pattern.…”
Section: Discussionmentioning
confidence: 99%
“…The assessment of diet quality among adolescents has tended to use both food and nutrient-based diet indices such as the Healthy Eating Index [11-13] and its derivatives [14,15]. These diet indices were adapted from those originally developed for adults based on the United States Dietary Guidelines.…”
Section: Introductionmentioning
confidence: 99%